Not in my backyard, but not far away from me: Local acceptance of wind power in China. (15th March 2015) - Guo, Yue; Ru, Peng; Su, Jun; Anadon, Laura Diaz
Abstract: Local acceptance of wind energy technology has become an important factor to consider when designing local and national wind energy technological innovation policies. Previous studies have investigated the factors that shape the local acceptance of wind power in high-income countries. However, to the best of our knowledge, these factors had not been investigated in China. Utilizing a survey and quantitative analysis, we have identified the factors that are correlated with local acceptance of wind power in China. We conducted our study in the city of Jiuquan, Gansu Province, which currently possesses the largest installed capacity for wind power generation in China. Two factors, namely, perceived economic benefits and perceived environmental costs, influence local acceptance of wind power in China most significantly. Local acceptance of wind power in China can be described as "not in my backyard, but not far away from me". In other words, the acceptance rate is lowest when the source of wind power is located in their village or community, highest when the project is located in their county and city and decreases for projects that are constructed further away. Highlights: We find the characteristics of local acceptance of wind energy in China based on the evidence from Jiuquan city. We characterize the local acceptance of wind power in China as "not in my backyard, but not far away from me". The perceived economic benefits and the perceived environmental costs are the two most significant factors. The public receives most of information about wind power from various governmental agencies.